Functional And Radiological Outcome of Schatzker Type V and VI Tibial Plateau Fracture Treated with Closed Reduction and Ilizarov Fixation with or without Minimally Invasive Screw Supplementation - Pandey, Suresh; Bidary, Suraj (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Controversy exists as to the best treatment approach for high-velocity tibial plateau fractures. This study was done to assess the functional and radiological outcome of Schatzker type V and VI tibial plateau fractures treated with closed reduction and Ilizarov ring fixation with or without cancellous screw supplementation. Methods: An analytical cross sectional study was conducted among 25 cases of both closed and open Schatzker type V and VI tibial plateau fractures treated with closed reduction and Ilizarov ring fixation with or without minimally invasive cannulated cancellous screw supplementation. The outcome variables analyzed were union time, knee range of motion, American Knee Society Score (AKSS), Rasmussen’s Radiological Score (RRS), and complications. Data analysis was done using SPSS-20. P-value <0.05 was considered as statistically significant. Results: There were 15 type V fractures, 10 type VI fractures, 21 closed fractures, and 4 open fractures. All the fractures united with a mean union time of 15.88 weeks (range 12-24). The mean American Knee Society score was 77.8 (range 68-95), Rasmussen’s radiological Score (RRS) 15.12 (range 10-18), and mean range of motion was 112.40 (range 90-135). Superficial pin site infection was present in 7 (28%) of the cases. There was no case of nonunion, deep infection, repeat surgery other than implant removal, or nerve palsy. Conclusions: Closed reduction and Ilizarov ring fixation with or without minimally invasive screw supplementation give rise to good to excellent functional and radiological outcomes in most of the cases in the treatment of Schatzker type V and VI tibial plateau fractures with minimal bone or soft tissue related complications.